If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 1 = 2r + -4y + 3t + -12 Reorder the terms: 1 + 2x = 2r + -4y + 3t + -12 Reorder the terms: 1 + 2x = -12 + 2r + 3t + -4y Solving 1 + 2x = -12 + 2r + 3t + -4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 2x = -12 + 2r + 3t + -1 + -4y Combine like terms: 1 + -1 = 0 0 + 2x = -12 + 2r + 3t + -1 + -4y 2x = -12 + 2r + 3t + -1 + -4y Reorder the terms: 2x = -12 + -1 + 2r + 3t + -4y Combine like terms: -12 + -1 = -13 2x = -13 + 2r + 3t + -4y Divide each side by '2'. x = -6.5 + r + 1.5t + -2y Simplifying x = -6.5 + r + 1.5t + -2y
| -3p+4=10 | | x=3r+4-y | | 4+11x=70 | | 5-y=4-9 | | 2b(0.5o)+a=35 | | Y=-x^2+6x-12 | | lnx=1+ln(x-4) | | x^2-1=1935 | | (y^2)-y-20=0 | | -10r+4=-56 | | 8*4=(y*7)-(y*3) | | 1/3(6-15x)=-3(x-3) | | 6x=732 | | 18s+24=168 | | 11x+1=738 | | 50x+20=1170 | | 12l+6=114 | | 3x+y=-9 | | 3(a-9)=90 | | x+5y-2x+4z-1=21 | | 13z+6u+8x+19+u= | | 15-5.2x=9+1.2x | | boa=450 | | (3x-1)/2=4(2x-5) | | 6m^2+12m-90=0 | | 2b-2o-2a=1 | | 10(4x+15)+11x-13= | | 4x+4=12x+4 | | 3r+9=4r-6 | | 3(85-y)+2y=190 | | 1.3a-12=4.3a+6 | | 0.5x+14=27 |